Rodent models of stress and dendritic plasticity – Implications for psychopathology - M.A. Laine; R.M. Shansky (Neurobiology of Stress, 2022)
Stress, as commonplace as it is, is a major environmental risk factor for psychopathology. While this association intuitively, anecdotally, and empirically makes sense, we are still very early in the process of understanding what the neurobiological manifestations of this risk truly are. Seminal work from the past few decades has established structural plasticity in the brain as a potential key mechanism. In this review we discuss evidence linking particularly chronic stress exposure in rodent models to plasticity at the dendrites, like remodeling of dendritic branches and spines, in a range of brain regions. A number of candidate mechanisms that seek to explain how stress influences neuroanatomy at this level have been proposed, utilizing in vivo, ex vivo and in vitro methods. However, a large gap still remains in our knowledge of how such dynamic structural changes ultimately relate to downstream effects such as altered affective and cognitive states relevant for psychopathology. We propose that future work expand our understanding of plasticity of specific stress-related brain circuits and cell-types. We also note that the vast majority of the work has been conducted solely on male rodents. The next big strides in our understanding of the neurobiology of psychopathology will require the inclusion of female subjects, as several studies have suggested both sex divergent and convergent features. By understanding plasticity, we can harness it. The growth of this body of knowledge will inform our efforts to improve the therapeutic options for stress-related psychopathology.